Mechanism of action of Imeglimin: A novel therapeutic agent for type 2 diabetes. Issue 3 (29th December 2020) - Hallakou‐Bozec, Sophie; Vial, Guillaume; Kergoat, Micheline; Fouqueray, Pascale; Bolze, Sébastien; Borel, Anne‐Laure; Fontaine, Eric; Moller, David E.
Abstract: Imeglimin is an investigational first‐in‐class novel oral agent for the treatment of type 2 diabetes (T2D). Several pivotal phase III trials have been completed with evidence of statistically significant glucose lowering and a generally favourable safety and tolerability profile, including the lack of severe hypoglycaemia. Imeglimin's mechanism of action involves dual effects: (a) amplification of glucose‐stimulated insulin secretion (GSIS) and preservation of β‐cell mass; and (b) enhanced insulin action, including the potential for inhibition of hepatic glucose output and improvement in insulin signalling in both liver and skeletal muscle. At a cellular and molecular level, Imeglimin's underlying mechanism may involve correction of mitochondrial dysfunction, a common underlying element of T2D pathogenesis. It has been observed to rebalance respiratory chain activity (partial inhibition of Complex I and correction of deficient Complex III activity), resulting in reduced reactive oxygen species formation (decreasing oxidative stress) and prevention of mitochondrial permeability transition pore opening (implicated in preventing cell death). In islets derived from diseased rodents with T2D, Imeglimin also enhances glucose‐stimulated ATP generation and induces the synthesis of nicotinamide adenine dinucleotide (NAD + ) via the 'salvage pathway'. In addition to playing a key role as a mitochondrial co‐factor, NAD + metabolites may contribute to the increase in GSIS (via enhanced Ca ++ mobilization). Imeglimin has also been shown to preserve β‐cell mass in rodents with T2D. Overall, Imeglimin appears to target a key root cause of T2D: defective cellular energy metabolism. This potential mode of action is unique and has been shown to differ from that of other major therapeutic classes, including biguanides, sulphonylureas and glucagon‐like peptide‐1 receptor agonists.